Immune Response Induced by Pure and Physical Detoxified S.aureus hemolysin Loaded on Calcium Phosphate Nanoparticles - Mohamad J. Khadum (Journal of Global Pharma Technology, 2019)
Α-hemolysin is one of the virulence factors that cause damage of RBC membranes. In the present study, S. aureus hemolysin was used as a model of toxin. Pathogenic strain of S. aureus, isolated from patient wounds, was used to produce α-hemolysin in tryptic soy broth medium. After 40 hrs of S. aureus growth, the supernatant was precipitated with 75% ammonium sulphate before purification by DEAE- cellulose and sephacryl-S200 chromatography. Detoxification of pure hemolysin by different temperature and two types of UV light had been achieved. Furthermore, calcium phosphate nanoparticles (CAP NPs) was prepared and used, as nanoadjuvant, to carry detoxified hemolysin. Scanning electron microscope (SEM), UV-VIS spectrophotometer, Zeta potential and X-ray diffraction (XRD) were used to characterize CAP and CAP/hemolysin complex. The CAP NPs appeared spherical in shape with diameter average 36-67nm, while, zeta potential of CAP NPs was -34.47 mV. The XRD patterns revealed the combination of CAP NPs with detoxified hemolysin and lost crystalline structure of CAP. Moreover, the combination was used to induce T-lymphocyte transformation and cytokines secretion in vitro. Lymphocyte proliferation with0.7 µg/ml of detoxified hemolysin increased proliferation 4.5 fold compared to negative control. On the other hand, 1.4 μg/ml of detoxified hemolysin stimulate the cytokines production of IL-1β and IL-6 to 16.4 and 18 pg/ml, respectively.Keywords: Immune response, Detoxification, Hemolysin, Calcium phosphate, Nanoparticles.